Religiosity of individuals hospitalized with acute coronary syndrome in an urgency and emergency hospital in Acre (Research, Society and Development, 2023)
The objective was to evaluate the religiosity of individuals hospitalized with acute coronary syndrome in an emergency hospital in Acre. This is a cross-sectional, descriptive study with a quantitative approach. The sample consisted of 65 individuals of both sexes. For data collection, the Portuguese version of the Duke religiosity scale (P-DUREL) and a form for collecting socio-demographic data were used. Most were aged between 50 and 60 years old 28 (43%), male 50 (70%), of brown race/skin color 42 (65%), with incomplete primary education 21 (32%) and the Catholic religion 33(51%). As for organizational religiosity, most demonstrated to attend church once a week 18 (28%). Faced with non-organizational religiosity, most evidenced carrying out individual religious activities 26 (40%). Regarding the intrinsic religiosity indexes, it was observed that the majority verbalized feeling the presence of God 56 (86%), that religious beliefs are really behind their whole way of living 41 (63%) and that the majority tries hard to live religion in all aspects of life 35 (54%). It is concluded that the religiosity of individuals hospitalized with acute coronary syndrome was considered satisfactory and may contribute to favorable health outcomes; however, in the present study, religion/religiosity did not influence cardiovascular risk.